Monitoring System Based on an IoT Platform for an AFPM Generator - Cumbajín, Myriam (2023)
In the present work, a monitoring platform is made for an Axial Flow Permanent Magnet (AFPM) Generator without magnetic core, the objective is to permanently monitor the values that come from the generator, where the generator variables have been acquired through an open source development board called Arduino MEGA, which sends the data to a Raspberry PI, where they are displayed and stored so that they can be processed. The variables are displayed using the graphical node-red environment that offers a very eye-catching dashboard, which will be displayed on a 7 in. liquid-crystal display screen. All the data obtained is stored in a database that will allow its use for specific purposes. The monitoring platform has been built with the ability to monitor the speed of the rotors, the voltage and the current of a phase and thus be able to process the total power supplied by the generator. As a result, the monitoring system is a promise component for Pico Hydro power station to control the power all the time provided by the Axial Flow Permanent Magnet Generator.